POOR PERFORMANCE OF A POPULAR MALARIA RAPID DIAGNOSTIC KIT COMPARED TO MICROSCOPY IN ADULTS P. FALCIPARUM INFECTIONS IN NIGERIA - Ajakaye, Oluwaremilekun Grace (FUDMA Journal of Sciences, 2024)
Rapid diagnostic tests (RDTs) have become the mainstay of malaria diagnosis, especially in endemic rural settings where microscopy is difficult to perform. However, the performance of malaria rapid diagnostic tests is infrequently accessed in adults in Nigeria. We therefore accessed the performance of CareStartTM malaria RDT in the routine detection of Plasmodium in adults. A total of 134 participants were tested for malaria infection using both microscopy and CareStartTM Malaria Pf (HRP2) Ag RDT (ACCESSBIO, USA) in Owo, Ondo State, Nigeria. The prevalence of malaria was higher based on microscopy (20.1%) compared to RDT (3.7%), with a mean parasite density of 2954.1 parasites per microliter of blood. The sensitivity and specificity of the RDT were 3.70% and 96.26%, respectively, while the positive predictive value and negative predictive value were 20.00% and 79.84%, respectively. Although RDT sensitivity varied significantly with parasite density, it failed to detect malaria infection with high parasitaemia. Our observation suggests possible reduced diagnostic sensitivity of RDT for the diagnosis of P. falciparum malaria in adults and the need to support the interpretation of RDT results with microscopy.